Melatonin significantly influences seed germination and seedling growth of Stevia rebaudiana Bertoni - Magdalena Simlat; Agata Ptak; Edyta Skrzypek; Marzena Warchoł; Emilia Morańska; Ewa Piórkowska (PeerJ, 2018)
Background Melatonin (MEL) is a signaling molecule in plants that affects developmental processes during vegetative and reproductive growth. Investigations have proved that exogenously applied MEL also has the potential to improve seed germination and plant development. Methods In the present study, seeds of stevia, a species with a very low germination rate, were germinated on an agar gel (AG) containing MEL at various concentrations (5, 20, 100, and 500 µM) in light. Seeds germinated on AG without MEL were used as controls. For the first 24 or 48 h of germination, the seeds were maintained in darkness as a pre-incubation step. Some seeds were not exposed to this pre-incubation step. Results At concentrations of 20 and 5 µM, MEL significantly improved germination, but only in seeds pre-incubated in darkness for 24 h (p < 0.001). At concentrations of 100 and 500 µM, MEL had an inhibitory effect on germination, regardless of the pre-incubation time. Melatonin also affected plantlet properties. At a concentration of 20 µM, MEL increased plantlet fresh weight and leaf numbers. At a concentration of 5 µM, it promoted plantlet height. Regarding root development, the most favorable MEL concentration was 500 µM. Biochemical analysis revealed that MEL promoted higher pigment concentrations but hampered superoxide dismutase activity. On the other hand, the concentrations of sugars and phenolics, as well as the activities of catalase and peroxidase, increased at a MEL concentration of 500 µM. Discussion The results suggest that MEL can improve germination of positively photoblastic stevia seeds and that it can play a role in plantlet development. However, the effects observed in the present study depended on the quantity of MEL that was applied.